1999
DOI: 10.1161/01.atv.19.10.2474
|View full text |Cite
|
Sign up to set email alerts
|

Detection, Quantification, and Characterization of Potentially Atherogenic Triglyceride-Rich Remnant Lipoproteins

Abstract: Abstract-Triglyceride-rich lipoprotein (TRL) remnants are formed in the circulation when apolipoprotein (apo) B-48 -containing chylomicrons of intestinal origin or apoB-100 -containing VLDL of hepatic origin are converted by lipoprotein lipase, and to a lesser extent by hepatic lipase, into smaller and more dense particles. Compared with their nascent precursors, TRL remnants are depleted of triglyceride, phospholipid, and C apolipoproteins and are enriched in cholesteryl esters and apoE. They can thus be iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
116
0
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(118 citation statements)
references
References 209 publications
0
116
0
1
Order By: Relevance
“…TGRL lipolysis during the postprandial state releases excess FFAs in the immediate proximity of the endothelium, which may cause endothelial injury (11) and subsequent endothelial dysfunction (32). In addition, TGRL remnants derived from TGRL lipolysis are themselves atherogenic (33,34), Endothelial cell cultures in 12-well plates were treated for 2 h with individual lipids isolated from VLDL (50 mg/dl TG) with or without 30 min incubation with LpL (2 U/ml). Each fraction was isolated from VLDL, evaporated, redissolved, and delivered to cells in a PBS vehicle (5 ml).…”
Section: Discussionmentioning
confidence: 99%
“…TGRL lipolysis during the postprandial state releases excess FFAs in the immediate proximity of the endothelium, which may cause endothelial injury (11) and subsequent endothelial dysfunction (32). In addition, TGRL remnants derived from TGRL lipolysis are themselves atherogenic (33,34), Endothelial cell cultures in 12-well plates were treated for 2 h with individual lipids isolated from VLDL (50 mg/dl TG) with or without 30 min incubation with LpL (2 U/ml). Each fraction was isolated from VLDL, evaporated, redissolved, and delivered to cells in a PBS vehicle (5 ml).…”
Section: Discussionmentioning
confidence: 99%
“…30 Increased RLP-C concentrations have been reported to be a significant and independent risk factor for coronary artery disease. 31 Recently, Stein et al 32 reported that RLP-C concentrations are significantly reduced after 6 weeks of therapy with atorvastatin or simvastatin, but not with pravastatin.…”
Section: Discussionmentioning
confidence: 99%
“…RLP-C is included in the measurement of non-HDL-C levels, a secondary treatment target after LDL-C lowering in hypertriglyceridemic patients (>200 mg/dl), as mentioned previously [74]. Additionally, following isolation from plasma, RLPs can be further characterized by various methods based on density, size, charge, apolipoprotein composition and immunoabsorption [108,109].…”
Section: Remnant-like Lipoproteins and Lipoprotein Subclass Distributiomentioning
confidence: 99%